Assessment Of Water Quality Status Of Penang Coastal Water - Suliman, Siti Noor Syafika (2018)
In this study, the assessment of water quality parameters (temperature, pH, salinity, conductivity, total dissolved solids (TDS), turbidity, dissolved oxygen, total suspended solids (TSS), chemical oxygen demand (COD), biological oxygen demand (BOD), ammonia, orthophosphate, nitrate, and nitrite) were carried out. Organic pollution index (OPI) was determined to assess the organic pollution status around the study area. Water samples were collected at the coastal water of Penang Second Bridge (Site A) and Penang National Park (Site B) during spring and neap tides,alternately for six months (December 2015 - May 2016).